1985
DOI: 10.3758/bf03207136
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language evidence for three factors in speech perception

Abstract: A continuing controversy concerns whether speech perception can be best explained by singlefactor psychoacoustic models, single-factor specialized linguistic models, or dual-factor models including both phonetic and psychoacoustic processes. However, our recent cross-language speech perception research has provided data suggesting that a three-factor model, including auditory, phonetic, and phonemic processing, may be necessary to accommodate existing findings. In the present article, we report the findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
249
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 290 publications
(260 citation statements)
references
References 29 publications
(41 reference statements)
9
249
1
1
Order By: Relevance
“…Limited training facilitated discrimination of the nonnative voicing distinction, but was totally ineffective at facilitating discrimination of the non-English retroflex/dental place distinction in this procedure (Werker et al, 1981). This set of results has been replicated using an additional non-English pla-ce-of-articulation distinction, the Interior Salish (Thompson or, in its native term, Inslekepmx) glottalized velar versus uvular distinction (/ki/-/qi/) (Werker & Tees, 1984a).…”
Section: Cross-language Speech Perception and Developmental Changesupporting
confidence: 59%
See 3 more Smart Citations
“…Limited training facilitated discrimination of the nonnative voicing distinction, but was totally ineffective at facilitating discrimination of the non-English retroflex/dental place distinction in this procedure (Werker et al, 1981). This set of results has been replicated using an additional non-English pla-ce-of-articulation distinction, the Interior Salish (Thompson or, in its native term, Inslekepmx) glottalized velar versus uvular distinction (/ki/-/qi/) (Werker & Tees, 1984a).…”
Section: Cross-language Speech Perception and Developmental Changesupporting
confidence: 59%
“…However, the Hindi informants reported that all these stimuli sounded like retroflex rather than dental stops. In subsequent synthesis attempts, stimuli were thus modeled more closely on the naturally produced retroflex and dental stops used in our previous work (Werker, Gilbert, Humphrey, & Tees, 1981;Werker & Logan, 1985;Werker & Tees, 1984a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I am far from the only one, because just as there were others in the 1980s who were looking at the psycholinguistic implications of cross-linguistic variation (e.g. Byrne and Davidson 1985;Werker and Logan 1985), so there have been many since, across a wide spectrum of psycholinguistic approaches, who have wrestled with the reconciliation of the universal and language-specific (Bowerman 1994;Emmorey 2002;Grimshaw 1997;Imai and Gentner 1997;Newmeyer 1998;Thornton et al 1998). The difference with the point where I started is that it would be unthinkable now to counter an experiment in Language A with an experiment in Language B without any mention of the language switch; even more satisfyingly, cross-language comparisons are found in all the psycholinguistic journals.…”
Section: The Universal Substratementioning
confidence: 99%